Bacterial L-forms on tap: an improved methodology to generate Bacillus subtilis L-forms heralds a new era of research - DEVINE, KEVIN (My University, 2012)
Bacterial L-forms are cell wall-less forms of bacteria that usually grow with a conventional cell wall. Despite being important for research, L-forms are difficult to generate reproducibly and research in this area is challenging. The manuscript published in this issue by Dominguez-Cuevas and colleagues reports a method to rapidly, quantitatively and reproducibly generate populations of L-forms in Bacillus subtilis. Importantly, the methodology may be applicable to other bacteria heralding a new era of L-form research. Moreover, the genetic requirements of this method provide insights into how Lipid II synthesis and autolysin expression/activity are normally balanced and the central role of the WalRK two-component system in this process.
PUBLISHED
Keywords: Immunology; Infection; Bacillus subtilis; Immunology, Inflammation & Infection